2013
DOI: 10.1021/ma400015d
|View full text |Cite
|
Sign up to set email alerts
|

Effective Light-Harvesting Antennae Based on BODIPY-Tethered Cardo Polyfluorenes via Rapid Energy Transferring and Low Concentration Quenching

Abstract: Light-harvesting antennae (LHA) were demonstrated using polyfluorenes (PFs) modified with borondipyrromethene (BODIPY) dyes tethered to the cardo structures. PFs work as a light absorber and an energy donor to the BODIPY units. The series of BODIPY-tethering PFs via the cardo carbon including homocardo PFs and alternative polymers with fluorene and the cardo fluorene were synthesized, and their optical properties were investigated. Initially, highly efficient energy transferring was observed from the PF main c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…The design and synthesis of the polymers is outlined in Scheme 1. The dibromo fluorene monomers with the BODIPY units were synthesized according to the literature [5]. All monomers were characterized by 1 H, 13 C and 11 B NMR spectroscopies and mass measurements, and it was concluded that pure monomers with the desired structures were obtained.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design and synthesis of the polymers is outlined in Scheme 1. The dibromo fluorene monomers with the BODIPY units were synthesized according to the literature [5]. All monomers were characterized by 1 H, 13 C and 11 B NMR spectroscopies and mass measurements, and it was concluded that pure monomers with the desired structures were obtained.…”
Section: Resultsmentioning
confidence: 99%
“…2,7-Dibromo-9,9-didodecylfluorene was obtained commercially, and used without further purification. 4,7-Bis-(3-hexylthiophen-2-yl) benzo[1,2,5]thiadiazole, monomers 1 and 2 were prepared according to the literature [5]. All reaction was performed under argon atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As we mentioned above, although organoboron complex-containing conjugated polymers have been studied as a versatile substance for fabricating advanced organic opto-electronic devices because of their superior optical properties and carrier-transport abilities, [73][74][75][76][77][78][79][80][81][82][83][84] ACQ problems remain as critical limitations to the practical use of these materials. In 2001, an AIE-active molecule was first reported.…”
Section: Conjugated Polymeric Materials Based On Group 13 Element-blocksmentioning
confidence: 99%
“…For example, a water-soluble conjugated copolymer (20) was obtained by Suzuki-Miyaura coupling copolymerization of a dibrominated diazaborole (Scheme 4c) [83]. Finally, Chujo and coworkers incorporated BODIPY chromophores as pendant groups to polyfluorenes by Ni-catalyzed Yamamoto or Suzuki-Miyaura coupling methods [84]. The polymers exhibited interesting energy transfer from the BODIPY side chains to the polyfluorene main chain.…”
Section: Side-chain Functionalization Of Conjugated Polymersmentioning
confidence: 99%